2013
DOI: 10.5194/bgd-10-9345-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Presence of <i>Prochlorococcus</i> in the aphotic waters of the western Pacific Ocean

Abstract: Prochlorococcus, the smallest but most abundant marine primary producer, plays an important role in carbon cycling of the global ocean. As a phototroph, Prochlorococcus is thought to be confined to the euphotic zone, with commonly observed maximum depths of ∼150–200 m. But here we show, using flow cytometry and cellular ribosomal content, for the first time the presence of abundant and active Prochlorococcus in the dark ocean ("deep Prochlorococcus" hereafter). Intensive … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 61 publications
(24 reference statements)
2
38
0
Order By: Relevance
“…Adding to the growing body of evidence that Prochlorococcus is found well below the euphotic zone (DeLong et al ; Shi et al ; Martínez et al ; Jiao et al ; Shibl et al ), we found Prochlorococcus and Synechococcus across a gradient of depths up to 1000 m at station ALOHA in the Pacific, as determined by both flow cytometric and metagenomic approaches. Prochlorococcus and Synechococcus concentrations were relatively consistent between 600 m and 1000 m depth, at 3–4 × 10 3 cells mL −1 and 2–6 × 10 2 cells mL −1 , respectively (Supporting Information Table S1).…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Adding to the growing body of evidence that Prochlorococcus is found well below the euphotic zone (DeLong et al ; Shi et al ; Martínez et al ; Jiao et al ; Shibl et al ), we found Prochlorococcus and Synechococcus across a gradient of depths up to 1000 m at station ALOHA in the Pacific, as determined by both flow cytometric and metagenomic approaches. Prochlorococcus and Synechococcus concentrations were relatively consistent between 600 m and 1000 m depth, at 3–4 × 10 3 cells mL −1 and 2–6 × 10 2 cells mL −1 , respectively (Supporting Information Table S1).…”
Section: Resultssupporting
confidence: 68%
“…Cells belonging to one of the LL clades (LLI, also known as ecotype eNATL2A), are relatively better adapted to vertically mixed waters than other LL‐adapted clades (Zinser et al ; Johnson et al ; Malmstrom et al ). While they are non‐motile and neutrally buoyant, Prochlorococcus and other cyanobacteria are subject to displacement by vertical mixing or attachment to sinking particles by phytodetritus (Lochte and Turley ; Vilibić and Šantić ; Jiao et al ). Thus, cyanobacterial cells likely get mixed below the euphotic zone for extended periods of time.…”
mentioning
confidence: 99%
“…Interestingly, Jiao et al . () analyzed aphotic regions of the Western Pacific using flow cytometry and molecular analyses and reported the presence of high‐light‐adapted Prochlorococcus cells at 500 m depth and significant amounts of HL II cellular rRNA at 300 m in the Luzon Strait. The abundance of Prochlorococcus in aphotic zones might also be attributed to their ability to import organic compounds as demonstrated by Gomez‐Baena et al .…”
Section: Resultsmentioning
confidence: 99%
“…In the summer SCS picoplankton occupy up to ~80% of the total autotrophic biomass in surface waters [ Wong et al ., ], raising the possibility of preferential export of small phytoplankton. In fact, the latest genomic study revealed that substantial amounts of Prochlorococcus populations can be found in the deep waters of the SCS and LS [ Jiao et al ., ], which is supportive of the hypothesis of δ 15 N sink shift by small phytoplankton although the mechanism is not well understood. Flow cytometry‐IRMS technique is not yet applied in the SCS to discern isotopic compositions of Prochlorococcus and picoeukaryotes.…”
Section: Discussionmentioning
confidence: 99%